A Life Worth Living with Dr David Mellor. Interview by Luna Allison, Canadian Federation for Animal Welfare. - Mellor DJ (Massey University)
Dr. David Mellor is a leading animal welfare thinker and the Foundation Director of the Animal Welfare Science and Bioethics Centre at Massey University’s Institute of Veterinary, Animal and Biomedical Sciences in New Zealand. Dr. Mellor has more than 50 years of teaching and research experience and has developed animal welfare standards, regulations and legislation internationally. He has been widely recognized for making major contributions to animal welfare around the world through consultation, teaching and more than 500 scientific publications. We sat down with Dr. Mellor during his time in Toronto this spring to discuss animal welfare in Canada and advancing our thinking for the betterment of animals.